ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN EARNINGS PADA PERUSAHAAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA (STUDI EMPIRIS PADA 110 PERUSAHAAN PERIODE 2006 – 2009) - Andy Yulius (Jurnal Akuntansi Bisnis, 2017)
This research wants to examine the effects of 5 company’s financial ratio to projected earning change of company. The hypothesis of this research are Current Ratio (CR), Total Asset Turnover (TATO), dan Return On Investment (ROI) have a positive influence to projected earning change of company (Future Earning). While Debt Equity Ratio (DER) and Price Earning Ratio (PER) has a negative influence to projected earning change of company. The technique for examining the hypothesis is multiple regression analysis by using SPSS 12.0 for windows.Key words : Current Ratio, Total Asset Turnover, Return On Investmen,t Debt Equity Ratio, Price Earning Ratio and Future Earning